Snakecharm - Atwater-Rhodes, Amelia (New York : Laurel-Leaf Books, 2006)
The peace forged by the love between Zane and Danica, leaders of the avian and serpiente realms that had been at war for generations, is threatened by the arrival of Syfka, an ancient falcon who claims one of her people is hidden in their midst. Syfka, an ancient falcon, has arrived from Ahnmik claiming that one of her people is hidden in their midst. The falcons are more powerful than the avians and serpiente combined, and Syfka shows nothing but contempt for Zane and Danica's alliance. To Zane's horror, his own people seem just as appalled as Syfka is by the thought of a mixed-blood child becoming heir to the throne. Is Syfka's lost falcon just a ruse to stir up controversy among them? The truth lies somewhere in their tangled pasts - and the search will redefine Zane and Danica's fragile future.
Keywords: Fantasy; Science fiction